WSU-EC Peace: It's Wonderful: Achieving University Nonviolence during Turbulent Times: The Spring and Fall Semesters of 1970 - Bartlett, Jeremiah (My University, 2008)
This paper examines student unrest and campus culture during the spring and fall semesters of 1970 at Wisconsin State University-Eau Claire (presently the University of Wisconsin-Eau Claire). Throughout the Vietnam War era, college students protested the war and the rise of U.S. militarism. Near the end of the 1960s and into the early 1970s, student protest on some of the nation’s campuses became increasingly violent. In the spring and fall semesters of 1970, for example, events on the campuses of Kent State University and the University of Wisconsin-Madison proved fatal. In a historical context, deadly protest characterized many universities’ 1970 spring and fall semesters. Conversely, the WSU-Eau Claire campus remained non-violent. This paper addresses the anti-war movement at the university level and details the main reasons WSU-Eau Claire maintained peace in a time of turmoil
Keywords: Wisconsin State University, Eau Claire.; Vietnam War, 1961-1975--Protest movements--Wisconsin--Eau Claire.; Student movements--Wisconsin--Eau Claire.; Peace movements--Wisconsin--Eau Claire.; Nonviolence--Wisconsin--Eau Claire.